Critical Discourse Analysis on Camila Cabello’s Song Lyric: “Havana” - Firma Pradesta Amanah (Yayasan Kyadiren, 2022)
This research aimed to find out the text analysis, social cognition, and context in Camila Cabello's song lyrics of Havana. This research belonged to descriptive qualitative. It was intended to describe precisely a phenomenon that was analysed. In conducting the research, the researcher operated the padan-intralingual and padan-ekstralingual methods. The discussion showed that Things observed in text analysis are: 1. macrostructure: theme, 2. superstructure: discourse structure, 3. microstructure: sentence form and meaning. This song's general theme tells about the dilemma of a girl who had to choose between her loved one or her hometown, Havana. Amid this dilemma, she was compelled to decide her hometown over the person she loved. Then about social cognition, the songwriter composed the Havana song based on her life experience. Havana, her hometown, was assembled as the general theme of this song. In this song, she appears incapable of leaving Havana even though she has already discovered her love from East Atlanta, Jeffery. Additionally, this song has become popular worldwide because of its uniqueness. Camila intended to show everyone that she loved her hometown, although there was a man that captivated her heart.